A pilot study for decellularizing porcine cornea for future use in corneal regeneration - Natasha Josifovska; Essi M. Niemi; Murugan Ramalingam; Geetha Manivasagam; Hanne Scholz; Goran Petrovski (PLoS ONE, 2025)
Porcine corneas were decellularized for future use in corneal regeneration by using various washing steps with 3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate (CHAPS) detergent, Benzonase, and Ethylenediaminetetraacetic acid (EDTA). The quality of the decellularized corneas was assessed by quantitative and qualitative measurement of DNA content, glycosaminoglycans (GAGs), immunofluorescent staining for Collagen (Col) I, V, Keratocan, Fibronectin, Laminin, Lumican and Decorin, and Transmission Electron Microscopy (TEM) to observe the structure of the collagen fibrils was used. The decellularization process showed 99.5% DNA content reduction in the corneas and a similar pattern was observed in the preservation of GAGs. Hematoxylin & Eosin (H&E) and immunofluorescent staining showed no presence of cell nuclei, while Alcian blue staining confirmed the presence of GAGs. Col I, V, Keratocan, Fibronectin, Laminin, Lumican and Decorin were still present in the decellularized corneas and TEM microscopy further confirmed the similar patterns of the collagen fibrils in the decellularized, compared to the native corneas. This pilot study showed our method is effective in decellularizing porcine corneas, with a very high amount of DNA being removed, while the GAGs being preserved to an acceptable extent, and the structure and pattern of the collagen fibrils maintained.